Health professionals wanted: Chain mobility across European countries - Isilda Mara (The Vienna Institute for International Economic Studies (wiiw), 2020)
This study analyses recent trends in the mobility of health professionals in Europe. It first identifies the drivers of this mobility, then analysis its main push-and-pull factors, and finally shows how different European countries are affected by these recent movements of health professionals. Our analysis focuses specifically on the patterns of mobility among medical doctors and nurses between 2010 and 2017. A number of indicators have been collected that provide a comprehensive picture of how the pattern of supply and demand for health professionals has changed over the past decade, illustrating the role that the mobility of health professionals across European countries plays in these developments. We find that a number of European countries have benefited from the mobility of health professionals, but this has accentuated imbalances in a number of other countries. Furthermore, a gravity model is used to identify the push-and-pull factors of mobility in a sample of 32 European countries over 2000-2017. Wage differentials in the health sector across the European countries certainly make some of the countries more successful at attracting health professionals than other countries that are failing to retain them. Consequently, the latter group of countries are facing huge challenges to provide health assistance to their own rapidly ageing populations.
Keywords: F22; J61; I15; I11; 330; health professionals; mobility; gravity modelling; European countries